Review: Animal health and sustainable global livestock systems - Perry, Brian D.; Robinson, Timothy P.; Grace, Delia (Elsevier, 2018)
This paper discusses the sustainability of livestock systems, emphasising bidirectional relations with animal health. We review conventional and contrarian thinking on sustainability and argue that in the most common approaches to understanding sustainability, health aspects have been under-examined. Literature review reveals deep concerns over the sustainability of livestock systems; we recognise that interventions are required to shift to more sustainable trajectories, and explore approaches to prioritising in different systems, focusing on interventions that lead to better health. A previously proposed three-tiered categorisation of ‘hot spots’, ‘cold spots’ and ‘worried well’ animal health trajectories provides a mental model that, by taking into consideration the different animal health status, animal health risks, service response needs and key drivers in each system, can help identify and implement interventions. Combining sustainability concepts with animal health trajectories allows for a richer analysis, and we apply this to three case studies drawn from North Africa and the Middle East; Bangladesh; and the Eastern Cape of South Africa. We conclude that the quest for sustainability of livestock production systems from the perspective of human and animal health is elusive and difficult to reconcile with the massive anticipated growth in demand for livestock products, mainly in low- and middle-income countries, as well as the aspirations of poor livestock keepers for better lives. Nevertheless, improving the health of livestock can contribute to health sustainability both through reducing negative health impacts of livestock and increasing efficiency of production. However, the choice of the most appropriate options must be under-pinned by an understanding of agroecology, economy and values. We argue that a new pillar of One Health should be added to the three traditional sustainability pillars of economics, society and environment when addressing livestock systems.